R8 development in the Drosophila eye: a paradigm for neural selection and differentiation. - Frankfort, B.J.; Mardon, G. (Development, 2002)
The Drosophila eye is an outstanding model with which to decipher mechanisms of neural differentiation. Paramount to normal eye development is the organized selection and differentiation of a patterned array of R8 photoreceptors - the founding photoreceptor of each ommatidium that coordinates the incorporation of all other photoreceptors. R8 development is a complex process that requires the integration of transcription factors and signaling pathways, many of which are highly conserved and perform similar functions in other species. This article discusses the developmental control of the four key elements of R8 development: selection, spacing, differentiation and orchestration of later events. New questions that have surfaced because of recent advances in the field are addressed, and the unique characteristics of R8 development are highlighted through comparisons with neural specification in other Drosophila tissues and with ganglion cell development in the mammalian retina.